2012
DOI: 10.1159/000338648
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Immunomodulatory Peptide IDR-1002 Enhances Monocyte Migration and Adhesion on Fibronectin

Abstract: Regulation of the immune system by immunomodulatory agents, such as the synthetic innate defense regulator (IDR) peptides, has been proposed as a potential strategy to strengthen host immune responses against infection. IDR peptides confer protection in vivo against a range of bacterial infections and have been developed as components of single-dose vaccine adjuvants due to their ability to modulate innate immunity, correlating with an increased recruitment of monocytes to sites of infection or immunization. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 90 publications
2
14
0
Order By: Relevance
“…In contrast, peptide-stimulated monocytes exhibited significantly stronger chemotactic activity towards CCL3 and CCL5 at nearly all chemokine concentrations tested. IDR-1002 stimulation in the absence of chemokines had no effect on baseline monocyte migration, confirming a previous study that showed the lack of direct chemokinetic properties of this peptide on monocytes [5]. Overall, these results demonstrated that IDR-1002 could selectively enhance monocyte migration towards chemokines CCL3 and CCL5.…”
Section: Idr-1002 Enhances Human Monocyte Chemotaxis Towards Ccl3 Andsupporting
confidence: 87%
See 2 more Smart Citations
“…In contrast, peptide-stimulated monocytes exhibited significantly stronger chemotactic activity towards CCL3 and CCL5 at nearly all chemokine concentrations tested. IDR-1002 stimulation in the absence of chemokines had no effect on baseline monocyte migration, confirming a previous study that showed the lack of direct chemokinetic properties of this peptide on monocytes [5]. Overall, these results demonstrated that IDR-1002 could selectively enhance monocyte migration towards chemokines CCL3 and CCL5.…”
Section: Idr-1002 Enhances Human Monocyte Chemotaxis Towards Ccl3 Andsupporting
confidence: 87%
“…Thus to understand the anti-infective nature of IDR-peptides, we sought to elucidate the mechanisms through which they enhance monocyte recruitment. In a previous study, we determined that IDR-1002, a peptide with no direct chemotactic or chemokinetic effects, augments monocyte migration through a fibronectin network via the promotion of b1-integrin-mediated adhesion [5]. Observations in this study also implicated an adhesion-independent, chemokine-specific mechanism utilized by IDR-1002 to promote monocyte recruitment.…”
Section: Introductionsupporting
confidence: 51%
See 1 more Smart Citation
“…IDR peptide 1002 is a synthetic cationic peptide derived from bovine bactenecin, a 12-amino-acid cathelicidin produced by bovine neutrophils [110][111][112]. Many research of angiogenesis and wound healing [110,113,114].…”
Section: Idr Peptide 1002mentioning
confidence: 99%
“…Many research of angiogenesis and wound healing [110,113,114]. There is evidence suggesting that IDR peptide 1002 is a better inducer of chemokines in vitro than IDR-1, another wellknown bactenecin-derived peptide [110,111,113]. In addition, IDR peptide 1002 protected mice against invasive Staphylococcus aureus and Escherichia coli infections by enhancing monocyte and neutrophil recruitment into the site of infection [110,111,113].…”
Section: Idr Peptide 1002mentioning
confidence: 99%